2022
DOI: 10.1088/2515-7620/ac3d3e
|View full text |Cite
|
Sign up to set email alerts
|

Can we save GHG emissions by working from home?

Abstract: Using data from official government publications in the UK, we estimate the potential changes in transport and buildings CO2e emissions in England and Wales if those engaged in jobs compatible with homeworking were to work mainly from home. We find that the net result is likely to be an increase, rather than a decrease in CO2e emissions. Assuming that 20% to 30% of workers were to work from home, the increase would range from 0.18% to 0.97% relative to emissions from the buildings and transport sectors combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This could perhaps be due to window opening (for fresh air) habits changing at extremely low temperatures, or additional rooms being heated. (Santos & Azhari, 2022) estimates an increase (0.11% to 0.6%) in total UK GHG emission in their scenario of increased homeworking across all sectors, based on assumption on increasing domestic demand through increased hours at home (where 62% of domestic demand is for space heating), however with space heating here not found to hugely increase, or indeed increase at all, this may be an overly pessimistic view. Analyses of both residential buildings and boilers found that electricity use and water heating did increase in lockdown, with increased free heat gains from this likely contributing to the lower heating season consumption.…”
Section: Discussionmentioning
confidence: 99%
“…This could perhaps be due to window opening (for fresh air) habits changing at extremely low temperatures, or additional rooms being heated. (Santos & Azhari, 2022) estimates an increase (0.11% to 0.6%) in total UK GHG emission in their scenario of increased homeworking across all sectors, based on assumption on increasing domestic demand through increased hours at home (where 62% of domestic demand is for space heating), however with space heating here not found to hugely increase, or indeed increase at all, this may be an overly pessimistic view. Analyses of both residential buildings and boilers found that electricity use and water heating did increase in lockdown, with increased free heat gains from this likely contributing to the lower heating season consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Hampton (2017) found that when working from home people were willing to use measures such as hot water bottles to keep warm, and it may be that these become insufficient below around 2.5°C, resulting in the increased space heating demand. Santos & Azhari (2022) estimate an increase (0.11-0.6%) in total UK greenhouse gas emissions in their scenario of increased homeworking across all sectors, based on an assumption on increasing domestic demand for electricity and gas through increased hours at home (where 62% of domestic demand is for space heating), and this is also raised as a concern by Erias & Iglesias (2022). However, with space heating here not found to hugely increase, or indeed increase at all, this may be an overly pessimistic view.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, shift B involved a raise in the heating load up to 82% for T set,h = 18 • C, although it could reduce the cooling load close to 50% compared to shift A for T set,c = 28 • C; work shift C, on the other hand, showed the most favorable pairs of heating and cooling demand, with heating loads close to the lowest of shift A and cooling loads close to the lowest of shift B, as depicted in Figure 6, standing out as the shift with optimal thermal loads. The work organization based on three working days implies a larger adoption of "work from home" arrangement, whose effectiveness in terms of work-life balance has already been demonstrated [41] as well as the increase in job satisfaction and employee well-being [42]. Regarding the environmental aspect, despite currently being a topic of great interest because there are many elements to be considered (e.g., commuting distance, private/public transport, HVAC plants, local emission factors, building insulation), enhancing remote working wherever possible could be a win-win pattern for both the employers and employees, in addition to the reduction in the energy consumption and greenhouse gas emissions related to the workers' transport [43].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 12, to satisfy the same thermal load, different plants can be used, each of which is characterized by an energy vector and a conversion efficiency: despite electricity being the carrier with the highest energy conversion factor, the coefficient of performance of the heat pumps was far better than the gas boilers based on the state-of-the-art. Therefore, the electric heat pump option for room heating appears to be the optimal approach from an environmental point of view [22,42]. Thus, the primary energy investigation generally suggests all-electric plants as being the most favorable, although it has been shown that, in some cases, plants supplied by natural gas also achieve a noticeable primary energy balance.…”
Section: Discussionmentioning
confidence: 99%